Breadnut Seed Flour (Artocarpus camansi): Potential Utilization as natural stabilizers to Impact the Physicochemical Properties and Organoleptic Value of Ice Cream - Kisworo, Djoko; Pertiwi, Indah Cahya; Bulkaini, Bulkaini; Fahrullah, Fahrullah; Nazir, Novizar (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study aimed to investigate the potential of breadnut seed flour (Artocarpus camansi) as a natural stabilizer in ice cream by evaluating its impact on physicochemical and organoleptic properties. A completely randomized design (CRD) was employed, with breadnut seed flour concentration as the single factor. Five treatment formulations were tested, consisting of varying ratios of skim milk to breadnut seed flour: 100:0 (P0, control), 87.5:12.5 (P1), 75:25 (P2), 67.5:32.5 (P3), and 50:50 (P4). The evaluated parameters included chemical properties (moisture, ash, and crude fiber content), physical properties (overrun and melting resistance), and organoleptic attributes (color, flavor, taste, and texture), assessed through both descriptive and affective methods. Data were analyzed using SAS software at a 5% significance level, with significant differences further examined using the Least Significant Difference (LSD) test. The results demonstrated that breadnut seed flour significantly influenced (p < 0.05) moisture, ash, crude fiber content, and descriptive evaluations of taste, flavor, texture, and color. Affective evaluations also indicated significant effects on flavor, texture, and color, though taste preference remained unaffected. The optimal formulation was the 12.5% breadnut flour treatment (P1), which exhibited favorable characteristics: 60.45% moisture, 1.96% ash, 0.86% crude fiber, 65.83% overrun, and 44.77 minutes of melting resistance. Organoleptically, this treatment produced ice cream with a creamy color, pleasant aroma, smooth texture, and high acceptability among panelists. These findings suggest that breadnut seed flour can effectively serve as a natural stabilizer in ice cream, with the 12.5% incorporation level providing the best balance of physicochemical and sensory properties. Contribution to Sustainable Development Goals (SDGs): SDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production